2010
DOI: 10.2169/internalmedicine.49.3457
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis in a Patient with Systemic Sclerosis and Primary Biliary Cirrhosis

Abstract: A 73-year-old woman who had been diagnosed with systemic sclerosis was admitted for further examination of bilateral hilar lymphadenopathy. Sarcoidosis was confirmed based on elevated serum levels of angiotensin-converting enzyme, a high proportion of lymphocytes and a high CD4/CD8 ratio in bronchoalveolar lavage fluid, abnormal 67 Gallium uptake in the mediastinum and noncaseating granulomas in skin biopsy specimens. In addition, high levels of antimitochondrial M2 antibodies and alkaline phosphatase indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
1
13
0
1
Order By: Relevance
“…Therefore, we scrutinized the previously reported 9 cases meeting this criterion (3,4). Although ILD existed in most of the cases, exacerbation of ILD that was probably due to sarcoidosis was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we scrutinized the previously reported 9 cases meeting this criterion (3,4). Although ILD existed in most of the cases, exacerbation of ILD that was probably due to sarcoidosis was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographically, 18 cases had ILD. Bilateral hilar lymphadenopathy (BHL) was found in 9 cases [2][3][4][5][6][7][8][9][10][11][12]. In our case, making the diagnosis of systemic sclerosis coincided with that of sarcoidosis, showing diffuse type of systemic sclerosis, elevation of serum ACE, and ILD without hilar adenopathy.…”
Section: Discussionmentioning
confidence: 70%
“…The association between systemic sclerosis and sarcoidosis has not been fully understood, but at least 24 cases Abbreviations are as follows: ACA anti-centromere antibody, ACE angiotensine converting enzyme, BHL bilateral hilar adenopathy, ILD interstitial lung disease suffering from both systemic sclerosis and sarcoidosis were found by review of literature [2][3][4][5][6][7][8][9][10][11][12]. The characteristics of the twenty-five cases including our case are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of SSc in patients with PBC is 3-8%. Conversely, the estimated prevalence of PBC among patients with SSc is 2.5-3% [13]. Although the subjacent immune mechanisms are not yet completely known, Mayo et al reported that antigen-stimulated T-cells play an important role and described bigger prevalence of clonal populations of CD8+ TCRBV3 in Reynolds syndrome than in both conditions alone [14].…”
Section: Discussionmentioning
confidence: 99%